Association of gout and colorectal cancer in Taiwan: a nationwide population-based cohort study - Chung-Yi Li; Jen-Pin Chuang; Jenq-Chang Lee; Tzeng-Horng Leu; Atik Choirul Hidajah; Ya-Hui Chang (BMJ Open)
Objectives This study aimed to determine colorectal cancer (CRC) risks among patients with gout through a follow-up study on a nationwide population-based cohort that included patients with gout and the general population in Taiwan.Participant From the Taiwan National Health Insurance Research Database, we identified 28 061 patients who were newly diagnosed with gout between 2000 and 2010 as the study cohort. We randomly selected 84 248 subjects matching in gender, age and baseline year as comparison cohort. The cohorts were followed up until CRC occurrence, withdrawal from the system of National Health Insurance, or Dec. 31, 2013.Primary and secondary outcome measures Cumulative incidences and incidence rate ratios (IRRs) of CRC between two cohorts were examined. The Cox proportional hazards model was used to evaluate risk factors associated with CRC development.Results During the 13-year follow-up, the incidence rate of CRC development in the gout cohort reached 2.44 per 1000 person-years, which was higher than the 2.13 per 1000 person-years in the control cohort (IRR=1.15; 95% CI 1.04 to 1.26). After adjusting for age, gender, urbanisation status and comorbidities, including hypertension, diabetes and hyperlipidaemia, gout showed no significant association with increased risk of CRC occurrence (adjusted HR=1.03; 95% CI 0.93 to 1.14).Conclusions Similar risks of CRC incidence were observed in patients with and without gout in Taiwan. Allopurinol and colchicine are commonly used as urate-lowering drug and anti-inflammation medication in Taiwan and had been shown to reduce the risk of CRC incidence. Thus, further pharmaco-epidemiological studies should be carried out to specifically assess the role of allopurinol in the relationship between gout and CRC.